2018
DOI: 10.2334/josnusd.17-0443
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet treatment restores bioactivity of titanium mesh plate degraded by contact with medical gloves

Abstract: Titanium mesh plate (Ti mesh) used for bone augmentation inadvertently comes into contact with medical gloves during trimming and bending. We tested the hypotheses that glove contact degrades the biological capability of Ti mesh and that ultraviolet treatment (UV) can restore this capability. Three groups of Ti mesh specimens were prepared: as-received (AR), after glove contact (GC), and after glove contact followed by UV treatment. The AR and GC meshes were hydrophobic, but GC mesh was more hydrophobic. AR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…UV light treatment has been reported to be an effective tool for cleaning accumulated organic contamination on medical devices. UV-treatment can remove hydrocarbon species from the surface of titanium and enhance bone conductivity [32][33][34][35][36]. Furthermore, photofunctionalization has yielded positive results in clinical studies [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…UV light treatment has been reported to be an effective tool for cleaning accumulated organic contamination on medical devices. UV-treatment can remove hydrocarbon species from the surface of titanium and enhance bone conductivity [32][33][34][35][36]. Furthermore, photofunctionalization has yielded positive results in clinical studies [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This process often accompany with various inconveniences and disadvantages: bending intraoperatively is time-consuming, which dramatically increases the patient's pain and the probability of infection; 78 imprecise shape made by manual bending is hard to completely fit the alveolar ridge, making the outcome of bone augmentation become empirical; careless contact with gloves during the bending process may also lead to the degradation of biological properties on titanium mesh. 79 In addition, the sharp edges on titanium mesh generated by the intraoperative bending are prone to cause mechanical stimulation on the mucosal flap, resulting in mucosal rupture and consequent exposure of the titanium mesh. 41 Therefore, with the development of clinical requirements and digital implantation technology, custom-made titanium mesh has become one of the research trends in GBR with titanium mesh.…”
Section: Progress In Digitizationmentioning
confidence: 99%
“…For the pollution caused by glove contact, although photofunctionalization cannot wholly remove the impurity particles on titanium, it can remove carbon and some other impurities, restore the biological activity of titanium mesh, and enhance its surface adhesion to osteoblasts. 79 Due to the simple procedure of photofunctionalization technology to treat titanium surface, and the consistently positive results in clinical studies of photofunctionalized titanium implants, clinical trials of photofunctionalized titanium mesh for bone augmentation are expected carrying out soon.…”
Section: Progress In Digitizationmentioning
confidence: 99%
“…Recent studies revealed that ultraviolet (UV) light treatment of titanium restored its superhydrophilicity after aging/storage [ 19 , 31 , 32 , 33 , 34 , 35 , 36 ]. UV treatment has also been reported to remove surface impurities (e.g., hydrocarbons) [ 32 , 37 , 38 , 39 , 40 ], thereby enhancing the biological activity of titanium for osteoblasts and bone [ 15 , 16 , 19 , 20 , 25 , 28 , 31 , 33 , 34 , 35 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that ultraviolet (UV) light treatment of titanium restored its superhydrophilicity after aging/storage [19,[31][32][33][34][35][36]. UV treatment has also been reported to remove surface impurities (e.g., hydrocarbons) [32,[37][38][39][40], thereby enhancing the biological activity of titanium for osteoblasts and bone [15,16,19,20,25,28,31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%